Protected areas and tourism in southern Africa : conservation goals and community livelihoods - Stone, Lesego Senyana; Stone, Moren T.; Mogomotsi, Patricia Kefilwe; Mogomotsi, Goemeone E.J. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This volume discusses the complex relationship between Protected Areas and tourism and their impact on community livelihoods in a range of countries in Southern Africa. Protected Areas and tourism have an enduring and symbiotic relationship. While Protected Areas offer a desirable setting for tourism products, tourism provides revenue that can contribute to conservation efforts. This can bring benefits to local communities, but it can also have a negative impact, with the establishment of Protected Areas leading to the eviction of local communities from their original places of residence, while also preventing them from accessing the natural resources they once enjoyed. Taking a multi-disciplinary approach, this book addresses the opportunities and challenges faced by communities and other stakeholders as they endeavor to achieve their conservation goals and work towards improving community livelihoods. Case studies from Botswana, Malawi, Namibia, South Africa, Tanzania, Zambia and Zimbabwe address key issues such as human-wildlife conflicts, ecotourism, wildlife-based tourism, landscape governance, wildlife crop-raiding and trophy hunting, including the high-profile case of Cecil the lion. Chapters highlight both the achievements and positive outcomes of Protected Areas, but also the challenges faced and how this is impacting how Protected Areas are viewed and also conservation priorities more generally. The volume gives these issues affecting Protected Areas, local communities, managers and international conservation efforts center stage in order inform policy and improve practice going forward. This book will be of great interest to students and scholars of conservation, natural resource management, tourism, sustainable development and African studies, as well as professionals and policymakers involved in conservation policy"--
Protected Areas and tourism dynamics in southern Africa: An overview / MOREN T. STONE, LESEGO S. STONE, GOEMEONE E. J. MOGOMOTSI AND PATRICIA K. MOGOMOTSI -- Protected Areas and Tourism Development: A Historical Analysis of the Southern African Experience / BOGA MANATSHA AND BONGANI GLORIOUS GUMBO -- Community perceptions of protected areas and tourism amidst poverty: Experiences from Southern Africa / HERBERT NTULI AND EDWIN MUCHAPONDWA -- Ecotourism as a paradigm shift in conservation and community livelihoods in the Southern African region: Opportunities, challenges and lessons learnt / SAID JUMA SULUO AND WINEASTER ANDERSON -- Tolerance for Wildlife Resources through Community Wildlife-Based Tourism: Implications for Sustainability / CHIEDZA NGONIDZASHE MUTANGA -- Landscape governance in sub-Saharan Africa / RENE VAN DER DUIM AND ARJAAN PELLIS -- In the Way of Wildlife: Contestations between Indigenous Peoples' Livelihood and Conservation / ONTHATILE OLERILE MOETI -- The socio-economic impacts of wildlife crop-raiding: An assessment of the efficacy of conservation and agricultural land uses reconciliation / EMMANUEL MWAKIWA -- Protected areas and community-based tourism: the effectiveness of current mitigation techniques in human wildlife conflicts / PATRICIA KEFILWE MOGOMOTSI -- Lifting of the hunting ban and the elephant debate in Botswana: Implications for conservation and development in southern Africa / JOSEPH ELIZERI MBAIWA AND EMMANUEL MOGENDE -- The role of the media and the international community in recent conservation issues in southern Africa: The case of Cecil the lion / GARIKAI CHIMUKA -- Nature-based tourism resources and climate change in southern Africa: -- Implications for conservation and development sustainability / KAITANO DUBE -- International organisations and the ivory sales ban debate: The case of Zimbabwe,Namibia and Botswana / CAROLINE COX -- The COVID-19 Pandemic and nature-based tourism in southern Africa / SUSAN SNYMAN -- The adoption of community-based tourism in the proximity of Protected Areas: Implications for policy and practice./ OLIVER MTAPURI -- Militarization of conservation and "shoot to kill" policies: An analysis of policy instruments on the environment and conservation in southern Africa / GOEMEONE, E.J MOGOMOTSI AND PATRICIA KEFILWE MOGOMOTSI -- Implications of the "High-value, Low-Volume" approach in conservation and tourism resources management / LESEGO, SENYANA STONE AND MOREN TIBABO STONE -- Promotion of pro-poor tourism in southern Africa: conservation and development critical issues / OWEN GOHORI, PEET VAN DER MERWE AND ANDREA SAAYMAN -- Contrasting safari and bushmeat hunting in southern Africa: Conservation and development issues / JULIA LAURA VAN VELDEN -- A synthesis of protected areas and tourism contributions to conservation and community livelihoods goals in southern Africa: A conclusion / MOREN TIBABO STONE, LESEGO SENYANA STONE, PATRICIA KEFILWE MOGOMOTSI, GOEMEONE EJ MOGOMOTSI.
Keywords: Protected areas -- Africa, Southern; Protected areas -- Economic aspects -- Africa, Southern; Protected areas -- Public use -- Africa, Southern; Sustainable tourism -- Africa, Southern; Wildlife conservation -- Africa, Southern; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism; BUSINESS & ECONOMICS / Green Business